PERANCANGAN SISTEM INFORMASI PENJUALAN TOKO ROTI ME TIME BERBASIS WEB - Agung Aushaaf Marshaa Hermanto; Indra Kanedi; Ricky Zulfiandry (Jurnal Media Infotama, 2023)
ABSTRACT: Technological developments mean that from time to time technology continues to develop in a more sophisticated direction. This development is based on human innovation and creativity, especially in the business field, many sales have been made on-line, this Me Time Bakery has not yet developed on-line sales, online developments or online stores through internet media have mushroomed in Indonesia, even already very well known by the general public. The number of various conveniences in shopping and the various types of products and services offered, make Indonesian people make online shops as one of the new "shopping places" besides shopping centers. this makes many online shop sellers competing to offer their products in various ways to attract consumers to shop, they take advantage of the situation where online shopping is currently in demand by the Indonesian people until now. The analysis of the old system at the Me Time Bakery is still manual by using a manual counting machine with a receipt system so that sales and purchases of stock items are re-corrected and recorded only on that day how many breads were sold, how many purchases and stock sales. To find out the availability of information products, with the Web-Based Me Time Bakery Sales Information System, it can facilitate the promotion process which has been conventional in nature. can use the application in accordance with accurate and good commands.